Predicting the biomechanical stability of IOLs inside the postcataract capsular bag with a finite element model. (June 2022) - Cabeza-Gil, I.; Calvo, B.
Highlights: Larger capsulorhexis makes the capsular bag more flexible C-loop designs tend to adjust to the equatorial bag diameter better than plate ones The fusion footprint of the capsular bag produces a mechanical perturbation to IOLs Graphical abstract: Abstract: Background and Objectives: Although cataract surgery is a safe operation in developed countries, there is still room for improvement in terms of patient satisfaction. One of the key issues is assessing the biomechanical stability of the IOL within the capsular bag to avoid refractive errors that lead to a second surgery. For that purpose, a numerical model was developed to predict IOL position inside the capsular bag in the short- and long-term. Methods: A finite element model containing the implanted IOL, the postcataract capsular bag, the zonules, and a portion of the ciliary body was designed. The C-loop hydrophobic LUCIA IOL was used to validate the numerical model and two more worldwide IOL designs were tested: the double C-loop hydrophobic POD FT IOL and the plate hydrophilic AT LISA IOL. To analyze the biomechanical stability in the long-term, the effect of the fusion footprint, which occurs days following cataract surgery, was simulated. Moreover, several scenarios were analyzed: the size and location of the capsulorexhis, the capsular bag diameter, the initial geometry of the capsular bag, and the material properties of the bag. Results: The biomechanical stability of the LUCIA IOL was simulated and successfully compared with the in vitro results. The plate AT LISA design deformed the capsular bag diameter up to 11.0 mm against 10.5 mm for the other designs. This design presented higher axial displacement and lower rotation, 0.19 mm and 0.2 ∘, than the C-loop design, 0.09 mm and 0.9 ∘ . Conclusions: All optomechanical biomarkers were optimal, assuring good optical performance of the three IOLs under investigation. Our findings showed that the capsulorexhis size influences the stiffness of the capsular bag; however, the shape in the anterior and posterior curvature surfaces of the bag barely affect. The results also suggested that the IOL is prone to mechanical perturbations with the fusion footprint, but they were not high enough to produce a significant refractive error. The proposed model could be a breakthrough in the selection of haptic design according to patient criteria.